Charles of Luxembourg and his gemstones - Ciulisová, Ingrid (2024)
One of the most influential fourteenth-century rulers, Charles of Luxembourg, king of Bohemia (1346–78), king of Romans (1346–8), and Holy Roman Emperor (1355–78), is well known as a collector of holy relics of Christendom. Less known is that, in addition to relics, he also sought out ancient coins, manuscripts and rare fabrics, jewels, objects of curiosity and, above all, gemstones. By his order, many of these gemstones were incorporated into composite virtuoso objects, reliquaries, and liturgical ornaments and thus converted to novel purposes. The book examines how the bejewelled precious objects supported Charles’s political agenda and self-image from a new transnational and interdisciplinary perspective